1999
DOI: 10.1152/jappl.1999.87.3.1213
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the insular cortex is affected by the intensity of exercise

Abstract: . Activation of the insular cortex is affected by the intensity of exercise. J. Appl. Physiol. 87(3): 1213-1219, 1999.-The purpose of this investigation was to determine whether there were differences in the magnitude of insular cortex activation across varying intensities of static and dynamic exercise. Eighteen healthy volunteers were studied: eight during two intensities of leg cycling and ten at different time periods during sustained static handgrip at 25% maximal voluntary contraction or postexercise cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
128
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(141 citation statements)
references
References 25 publications
9
128
0
2
Order By: Relevance
“…38). It has been a matter of debate whether physical activity is associated with an overall activation of the brain (30,39), but it is incontrovertible that exercise activates several regions of the brain in an intensity-dependent manner (16,44,57). Although the mechanical power output remained constant during exercise, increased difficulty in retaining power at the end of the hyperthermic cycle trial was reflected in the subjects' RPE, and it appears that brain areas associated with "central command" are activated when the "mental effort" associated with exercise is enhanced (58).…”
Section: Discussionmentioning
confidence: 99%
“…38). It has been a matter of debate whether physical activity is associated with an overall activation of the brain (30,39), but it is incontrovertible that exercise activates several regions of the brain in an intensity-dependent manner (16,44,57). Although the mechanical power output remained constant during exercise, increased difficulty in retaining power at the end of the hyperthermic cycle trial was reflected in the subjects' RPE, and it appears that brain areas associated with "central command" are activated when the "mental effort" associated with exercise is enhanced (58).…”
Section: Discussionmentioning
confidence: 99%
“…In normal humans, rCBF in the right insula covaries with heart rate (Critchley et al, 2000). Functional magnetic resonance imaging (fMRI) recently confirmed the functional links between the insular cortex and the modulation of heart rate (Williamson et al, 1997(Williamson et al, , 1999Critchley et al, 2000). The activity in the left insula increases during dynamic exercise (cycling) but not passive exercise (cycling movement induced by moving pedals independently) (Williamson et al, 1997(Williamson et al, , 1999.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…Intraoperative electrical stimulation of the insula elicits changes in heart rate and blood pressure (Oppenheimer et al, 1992). In normal subjects, functional neuroimaging studies showed that in response to physical exercise (Williamson et al, 1997(Williamson et al, , 1999 and mental stressor tasks (Critchley et al, 2000), both associated with significantly increased heart rate, the activity in both insula covaried with heart rate.…”
Section: Introductionmentioning
confidence: 99%
“…While activity of the insula has been linked to exercise-induced hypertension (Williamson et al, 1999), bradycardia (Volkow et al, 2000), and heart-rate variability (Critchley et al, 2003;Chang et al, 2013), we are not aware of any studies that have found low-level changes in physiology (eg, tachycardia or hypertension) to change insula connectivity per se (ie, when taking the insular cortex as a seed region of interest).…”
Section: Limitations and Future Directionsmentioning
confidence: 97%